The action of adenosine in relation to that of insulin on the low-Km cyclic AMP phosphodiesterase in rat adipocytes. - Wong, E H (1985)
The adenosine-sensitive cyclic AMP phosphodiesterase of rat adipocytes was found to reside in the same subcellular fraction as the enzyme sensitive to insulin. There were several similarities between the action of adenosine and that of insulin on the enzyme. The action of adenosine on the phosphodiesterase is probably like that of insulin, both being receptor-mediated, although different sites or different receptors could be involved. Adenosine analogues with intact ribose but a modified purine moiety elicited a response similar to that of adenosine. Added Ca2+ was also not a requirement for the action of adenosine. The action of adenosine was not synergistic with that of insulin, neither was adenosine essential for insulin action. Insulin stimulated the enzyme even at low cell concentrations and in the presence of adenosine deaminase. Adenosine, however, enhanced the effect of insulin, but only at insulin concentrations that produced submaximal effects. Thus the mechanisms of action could be similar or related. The time-course effect of a suboptimal concentration of insulin was transitory, like that of adenosine, and was influenced by the presence of adenosine, whereas that of a maximally effective concentration of insulin was sustained for at least 20 min and was not affected by the presence of adenosine. Isoprenaline enhanced phosphodiesterase activity stimulated by optimal concentrations of either adenosine or insulin, suggesting that their effects were mediated through different mechanisms of action.